Phase separation of metastable CoCrFeNi high entropy alloy at intermediate temperatures - He, Feng; Wang, Zhijun; Wu, Qingfeng; Li, Junjie; Wang, Jincheng; Liu, C.T. (Scripta materialia, 2017)
CoCrFeNi alloy is an exemplary stable base for high entropy alloys (HEAs), but its phase stability is still suspicious. Here, the CoCrFeNi HEA was firstly identified to be thermally metastable at 750°C. Composition decomposition occurred after annealed at 750°C for 800h. The minor addition of Al accelerated the composition decomposition and a second fcc phase with a different lattice constant occurred in the long time annealed CoCrFeNiAl0.1 HEA. The CoCrFeNi HEA cannot be seen as stable alloys anymore and researchers should be very careful when using the current phase selection models to predict stability of HEAs at intermediate temperatures. Composition decompositon occurred in the CoCrFeNi high entropy alloy after annealed at 750°C for 800h (see (a, b)). The addition of Al accelerated the decomposition and a second fcc phase with different lattice precipitated from the CoCrFeNi base, as shown in (c and d). These results indicated that the CoCrFeNi high entropy alloy is a metastable solid solution. [Display omitted]